A Label‐free Electrochemiluminescence Sensing for Detection of Dopamine Based on TiO2 Electrospun Nanofibers. Issue 1 (25th November 2021) - Fan, Xuemei; Sun, Nan; Wang, Shumin; Xu, Min; Zuo, Cheng; Xu, Xiaojuan; Li, Zhejian; Sun, Qiangqiang; Wang, Yimeng; Liu, Ping; Fan, Xinhui
Abstract: TiO2 electrospun nanofibers (TiO2 ENNFs) were synthesized with titanium tetraisopropoxide as precursor by an electrospinning process and characterized by SEM, TEM, XRD, XPS, FT−IR, UV and FL. For the excellent properties of film formation, Nafion/TiO2 ENNFs modified electrode was constructed, which exhibited an excellent electrochemiluminescence (ECL) performance and stability while K2 S2 O8 as co‐reactant. In the presence of dopamine (DA), the ECL signal quenched, which was due to that DA easily can be oxidized by holes generated by S2 O8 2− in electrode surface, thereby inhibiting the formation of TiO2 * . Based on this, a new ECL method was proposed for DA detection with a linear range from 0.033 μM to 6.7 μM. The detection limit was 0.017 μM and it was applied in the detection of DA in dopamine hydrochloride injection with satisfactory results. Abstract :